PERAN OAS (ORGANIZATION OF AMERICAN STATES) DALAM MENANGANI KRISIS PENGUNGSI VENEZUELA TAHUN 2017-2023 - Yovana, Kesi; Athallah, Muhammad Fadhil (Universitas Prof. Dr. Moestopo (Beragama), 2023)
The aim of this research is to investigate how the Organization of American States (OAS) played a role in addressing the refugee crisis originating from Venezuela in the regional American area from 2017 to 2023. Additionally, this research will identify various factors influencing the OAS's response to the Venezuelan refugee situation. This involves considering both internal and external factors, including the internal political dynamics of the OAS, pressure from member states, the role of external actors, and the impact of public opinion on the response. The method used in this research is qualitative with a descriptive approach. In this method, the author involves the collection and analysis of data from sources such as direct interviews with Venezuelan representatives in Indonesia, journals, books, documents, reports, and scholarly works. Observations are conducted by analyzing descriptive data, and the final research results will be based on the data studied.